Analisis Strategi Pengelolaan Badan Usaha Milik Desa Tani Unggul Desa Banjardowo Jombang - Lina Susilowati; Yulia Effrisanti; Munawaroh Munawaroh (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2022)
One of the government policies in improving the local economy is the establishment of BUMDes. The Village Owned Enterprise (BUMDes) Tani Unggul Desa Banjardoro, Jombang District is an institution that aims to strengthen the economy of rural communities which was formed based on the needs and potential of the village where the community and village government are the managers. The research problem is to determine the management strategy of the Banjardowo Village Owned Enterprise, Jombang District. The research design uses a quantitative, where data collection uses a questionnaire given to respondents. The Process Hierarchy Analysis (AHP) technique is used to determine decisions regarding the right strategy in the management of BUMDesThe results showed that there were 6 management strategies of Tani Unggul Village Owned Enterprises (BUMDes) in Banjardowo Village, Jombang District, Jombang Regency, namely Accountable, Participatory, Transparent, Cooperative, Sustainable and Emancipatory. Management strategy for the accountable field is to complete financial instruments. The participatory field is BUMDes expanding the business area and assisting community business development. The transparent area is that BUMDes communicate developments and other information from the program directly to BUMDes consultants. The cooperative field is the Organizational Structure that meets the needs of BUMDes. The sustainable field is there is business continuity. The emancipatory sector is profit for the owners of capital according to the percentage of capital participation.